(3GdhGbY GdETcGdj dJYdje efgGL GdadSaI aj GdUqa GdKGfhqj GdKGdK aj GdKGfhqjGJ GddHfGfqjI, eG HYO GdYGe (B1999(3, heLGdGJ JWhjQgs - (3eGdc, HjGQs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3GdeYgO GdYGdj ddOcJhQGg aj GdBOGH hGdYdhe GdEfSGfnqjIs, 2014)
(3JJeMhQ gPg GdCWQhMI Mhd JYdje GdadSaI aj GdeQMdI eG bHd GdLGeYjI(B. (3dbO QqcRJ Ydi GdYKQGJ GdJj jYGfj efgG gPG GdJYdje, hMGhdJ TQM GdCSHGH GdJj CqOJ Edi HQhR gPg GdYKQGJ, EfWdGbG ef hGbY GdadSaI, GdPj jYJHQ ETcGdjG HMqO PGJg, eQhQG HJYdjeg GdPj jMed aj WjGJg ETcGdjGJ YOjOI, hUhdG Edi SjGSGJ GdOhd GdJj Jbdd ef GdGgJeGe HGdaQhY GdCOHjI, MjK JJQqHY GdadSaI Ydi YQT GdUOGQI Vef ehGO gPg GdaQhY, gPG ef LgI(B. (3hef LgI CNQi, JfGhdJ gPg GdCWQhMI hGbY JYdje GdadSaI aj dHfGf, hJMOjOG aj GdeQMdI GdKGfhjI; aCVGAJ Ydi GdUYhHGJ GdJj jYGfj efgG GdefgGL GdMGdj, GdeYJeO efP GdYGe (B1999(3, NUhUG dLgI YOe GdJWGHb Hjf CgOGag, hHjf GdCgOGa GdehVhYI dJYdje GdadSaI HTcd YGe(B. (3dbO bqSeJ gPg GdCWQhMI Edi bSejf(B: (3GdbSe GdChd(B: (3JfGhd GdTb GdfXQj, hJQcR Ydi cd eG cJHg GdadGSaI hGdJQHhjhf GdYGedhf aj Mbd GdadSaI Yf gPG GdJYdje, hLQi GdJQcjR Ydi ETcGdjGJg, hWQbg, hefgLjGJg, hcjajI Jbjjeg, hcjajI EYOGO GdCSGJPI dg; ceG LQi JMOjO CgOGa gPG GdJYdje hcaGjGJg(B. (3GdbSe GdKGfj(B: (3JfGhd GdTb GdYedj, hbO JeMhQ Mhd GdefgGL GddHfGfj, HTcd NGU, HOAG ef JGQjNjJg, eQhQG HeVehfg, hUhdG Edi eOi GdJWGHb Hjf CgOGag heMJhGg hWQb Jbjjeg, hHjf GdCgOGa GdehVhYI dJYdje GdadSaI(B. (3hde jZad gPG GdbSe Yf GdCYeGd GdejOGfjI, EP JVef fJGFL GSJeGQJjf CLQjJG eY GdCSGJPI hGdeJYdejf, HGdEVGaI Edi ebGHdGJ YOjOI eY HYV Gdbqjejf Ydi gPG GdefgGL hJbjjeg(B. (3hGNJJeJ GdCWQhMI HHYV GdGbJQGMGJ GdJj JMJGL Edi eRjO ef GdJWhjQ(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: Cycle Secondaire L$1 (Benseignement de la Philosophie et la Morale Curriculums; Secondary Education Philosophy and Moral Education Curricula; (3GdeQMdI GdKGfhjI JYdje GdadSaI hGdGNdGb GdefGgLs